The digital classification of “unknown maker(s)” of cultural objects: A case study of Iziko South African National Gallery - Moruthane, Sepadi (Department of Knowledge and Information Stewardship, 2021)
Throughout history, cultural institutions like the Iziko Museums of South Africa have preserved, catalogued, researched and displayed a diverse collection of cultural objects. The renewed interest in digital media has revived the move to reclaim cultural identities, bringing with it the associated challenges regarding the veracity of historical accounts. With the transition to digitisation, and the adoption of digital curatorship for knowledge production in museum environments, it has become necessary to examine the historical accuracy, reliability and trustworthiness of the digital information being provided. Digitisation is an important priority for most cultural institutions. This study contributes to the colonial debate about museum classification and the challenges that these institutions face regarding what is referred to as the “unknown maker”. The use of the term “unknown maker(s)” to denote creators of cultural objects housed in the Iziko South African National Art Gallery collections was crucial to this investigation into the digital cataloguing of objects whose creators could not be determined. The findings show that a national museum is a space where identities are contested, and that museum professionals are repeatedly faced with difficult curatorial and ethical decisions when it comes to classifying cultural objects. As a result, the problems encountered with the digitsation and cataloguing of cultural objects are extensive. Inaccurate classification processes, including the use of the term “unknown maker(s)”, affects how digital heritage objects are recorded, the servicesthat museums offer, how exhibitions are presented, the research that is undertaken, and the skills required to manage cultural objects.